Physiological investigations of the influences of byproduct pathways on 3‐hydroxypropionic acid production in Klebsiella pneumoniae. (16th October 2019) - Li, Xiaohan; Chen, Liuni; Wang, Xiuling; Tian, Pingfang
Abstract: Klebsiella pneumoniae can naturally synthesize 3‐hydroxypropionic acid (3‐HP), 1, 3‐propanediol (1, 3‐PD), and 2, 3‐butanediol (2, 3‐BD) from glycerol. However, biosynthesis of these industrially important chemicals is constrained by troublesome byproducts. To clarify the influences of byproducts on 3‐HP production, in this study, a total of eight byproduct‐producing enzyme genes including pmd, poxB, frdB, fumC, dhaT, ilvH, adhP, and pflB were individually deleted from the  K. pneumoniae genome. The resultant eight mutants presented different levels of metabolites. In 24‐h shake‐flask cultivation, the adhP ‐ and pflB ‐deletion mutants produced 0.41 and 0.44 g/L 3‐HP, respectively. Notably, the adhP and pflB double deletion mutant K. pneumoniae Δ adhP Δ pflB produced 1.58 g/L 3‐HP in 24‐h shake‐flask cultivation. When K. pneumoniae Δ adhP Δ pflB was harnessed as a host strain to overexpress PuuC, a native aldehyde dehydrogenase (ALDH) catalyzing 3‐hydroxypropionaldehyde (3‐HPA) to 3‐HP, the resulting recombinant strain K. pneumoniae Δ adhP Δ pflB (pTAC‐puuC) (pTAC‐puuC is PuuC expression vector) generated 66.91 g/L 3‐HP with a cumulative yield of 70.84% on glycerol in 60‐h bioreactor cultivation. Additionally, this strain showed 2.3‐, 5.1‐, and 0.67‐fold decrease in the concentrations of 1, 3‐PD, 2, 3‐BD, and acetic acid compared with the reference strain K. pneumoniae (pTAC‐puuC). These results indicated that the byproducts exerted differential impacts on the production of 3‐HP, 1, 3‐PD, and 2, 3‐BD. Although combinatorial elimination of byproduct pathways could reprogram glycerol flux, the enzyme 1, 3‐propanediol oxidoreductase (DhaT) that catalyzes 3‐HPA to 1, 3‐PD and the enzymes ALDHs, especially, PuuC are most pivotal for 3‐HP production. This study provides a deep understanding of how byproducts affect the production of 3‐HP, 1, 3‐PD, and 2, 3‐BD in K. pneumoniae .